If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -7x = y Solving 6 + -7x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -7x = -6 + y Combine like terms: 6 + -6 = 0 0 + -7x = -6 + y -7x = -6 + y Divide each side by '-7'. x = 0.8571428571 + -0.1428571429y Simplifying x = 0.8571428571 + -0.1428571429y
| (-4(8))(-30)-(-8)=x | | 2/15=21/15 | | -3-x/4=-x | | 40=1.6u | | -13+23=-2(x+3) | | 3x-2/5 | | 3x-2/5=21/15 | | -9-4-19= | | 9=9x-10 | | 172-x=234 | | -10-2x=10 | | 5/2=4/x | | 7/3-x/7 | | -9x/5=18 | | -40/(-12-8) | | y/5=y/4+4 | | 3-x+4-16=-2X+14-6 | | -2(18-3y)=7y+27 | | y/5=y/4+5 | | 3/11x+13=20 | | y/2.5=8 | | 4x+4(x+10)=480 | | 8x-44=6x-6 | | 274=-x+33 | | 18x-9=5x-1+3x | | 7+4(-6)= | | x=v-10 | | 31=6y+2x | | 26-w=209 | | x/2-9/10=x/5 | | T=1/6(x-y+z) | | 7w/6+3=5w/4 |